GURU PROFESSIONAL DALAM PERSPEKTIF HADITS TARBAWI (TELAAH DALAM KITAB SUNAN AT-TURMUDZI KARYA SYEKH ABU ISA MUHAMMAD IBNU ISA IBNU SAURAH) - Nasution Nasution (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2021)
This paper examines the teacher figure and the concept of teachers according to Sunan At Tarmidzi in relation to the professionalism of Islamic Religious Education teachers in formal schools. This study aims to get an overview of the teacher's figure through the study of the hadith tarbawi as well as to get an explanation of the concept of the teacher and to prove the strengths and weaknesses of the tarbawi hadith in relation to the professionalism of the Islamic Religious Education teachers. The method used in this study is to use the library research model (literature study), content review and data analysis with the object of study which contains tarbawi hadiths about the figure of a teacher and its role. The results of this study explain that At-Tirmidzi calls teachers waratsatu al-anbiya (heirs of the prophets). it is natural that the teacher gets an appropriate reward and reply. In addition, professional teachers must have intellectual abilities, lifting moral values that are absolutely must be owned by professional teachers, namely sincerity and humility. While the weaknesses of the tarbawi hadiths about teachers in the above history are related to the professionalism of Islamic Religious Education teachers, it appears in the details on the characteristics of a teacher.Keywords: professional teacher, Hadits Tarbawi AbstrakTulisan ini mengkaji sosok guru dan konsep guru menurut Sunan At Tarmidzi dalam kaitannya dengan profesionalisme guru Pendidikan Agama Islam di sekolah formal. Penelitian ini bertujuan untuk mendapatkan gambaran tentang sosok guru melalui kajian tarbawi hadits serta untuk mendapatkan penjelasan tentang konsep guru dan untuk membuktikan kelebihan dan kekurangan hadits tarbawi dalam kaitannya dengan profesionalisme umat Islam. guru Pendidikan Agama. Metode yang digunakan dalam penelitian ini adalah dengan menggunakan model penelitian kepustakaan (literature study), telaah isi dan analisis data dengan objek kajian yang memuat hadits-hadits tarbawi tentang sosok guru dan perannya. Hasil penelitian ini menjelaskan bahwa At-Tirmidzi menyebut guru waratsatu al-anbiya (pewaris para nabi). wajar jika guru mendapat reward dan reply yang sesuai. Selain itu, guru profesional harus memiliki kemampuan intelektual, mengangkat nilai-nilai moral yang mutlak harus dimiliki oleh guru profesional, yaitu keikhlasan dan kerendahan hati. Sedangkan kelemahan hadits-hadits tarbawi tentang guru dalam riwayat di atas berkaitan dengan profesionalisme guru Pendidikan Agama Islam, tampak pada rincian karakteristik seorang guru.Kata Kunci: guru professional, hadits tarbawi